Psychology of music: From sound to significance - Tan, Siu-Lan; Pfordresher, Peter; Harré, Rom (Hove Psychology Press, 2010)
Why are some disturbances of air molecules heard as 'noise' while others are perceived as music? What happens at the level of the sound wave, the ear, and the brain when we perform or listen to music? How do musical abilities emerge and develop, and become refined as one acquires musical expertise? And what gives music its deep emotional significance and its power to influence social behavior, across vastly different cultural contexts? These are some of the primary questions defining the field called 'the psychology of music' and driving the present volume.This book provides an introduction to classic and current studies in the psychology of music, combining a comprehensive summary with critical assessments of existing research. The volume captures the interdisciplinary breadth of the field, while covering central topics in depth. Part One explores sound and music at an acoustic level, explaining auditory events with respect to the workings of the ear and brain. Part Two focuses on perception and cognition of melody, rhythm, and formal structure. Part Three examines the emergence and development of musical skills, and turns to the most practical aspects of psychology of music: music practice and performance. Finally, Part Four broadens the discussion to the question of meaning in music, with respect to its social, emotional, philosophical, and cultural significance. Throughout, both behavioral and neuroscientific perspectives are developed.This book will be invaluable to undergraduate and postgraduate students in the fields of psychology and music, and will appeal to anyone else who is interested in the psychology of music.